Pengukuran Tingkat Partisipasi Masyarakat Desa Cibedug, Kabupaten Bogor dalam Pembangunan Jalan Desa Tipe Otta Seal - Asjhari, Ahsan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2013)
Roads are the infrastructure needed to support rural connectivity. Roads open access to the market, education, and healthcare facilities to develop socioeconomic communities in the area. The technology used to open to penetrate rural areas up to the remote, it takes the road with low traffic volume specifications. One of the technologies of road pavement to support the road specification is otta seals that developed by Pusjatan Balitbang PU. In 2011, the technology was applied to build the rural road in Desa Cibedug, Kabupaten Bogor as a pilot project. This study aims to determine the level participation villagers Cibedug in the construction process using the combination of level participation stair by Arnstein and participatory road scheme. This study categorizes participation into three levels, i.e. high, medium, and low. Based on the results of the discussion, it can be seen that the participation of the villagers of Cibedug in most phases of construction is medium category. Meanwhile in the phase of action plan, participation of community was categorized as high, which can be seen through various forms of material and non-material participation deployed. Thus community participation has an important role in the successful development of rural roads.